1998
DOI: 10.1046/j.1365-2249.1998.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to carbonic anhydrase II is present in primary biliary cirrhosis (PBC) irrespective of antimitochondrial antibody status

Abstract: Antibody to carbonic anhydrase II, an enzyme abundantly present in biliary epithelium, has been proposed as a diagnostic marker for antimitochondrial antibody-negative PBC. In this study we determine its prevalence and clinical significance in a large series of patients with antimitochondrial antibody-positive and -negative PBC. Reactivity to carbonic anhydrase II was sought by Western immunoblotting in sera from 215 consecutive patients with PBC (26 antimitochondrial antibody-negative), 13 with autoimmune hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 33 publications
(49 reference statements)
0
20
0
Order By: Relevance
“…Initially the confirmation of the assay on a wide random patient population would be advisable, considering that 30 AMA-negative patients are representative for 600 patients with PBC. Subsequently, several minor autoantigens, [28][29][30] including a vast array of nuclear antigens, 12,31 could be added to the bead panel in the attempt to generate a comprehensive PBC assay or an autoimmune liver assay. The development of such a panel would permit the definition of autoantibody status with a single assay, importantly simplifying and accelerating diagnostics in autoimmune liver conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Initially the confirmation of the assay on a wide random patient population would be advisable, considering that 30 AMA-negative patients are representative for 600 patients with PBC. Subsequently, several minor autoantigens, [28][29][30] including a vast array of nuclear antigens, 12,31 could be added to the bead panel in the attempt to generate a comprehensive PBC assay or an autoimmune liver assay. The development of such a panel would permit the definition of autoantibody status with a single assay, importantly simplifying and accelerating diagnostics in autoimmune liver conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-six patients were studied: 33 rheumatoid arthritis (RA), 8 psoriatic arthritis (PA), 8 ankylosing spondilitis (AS), 23 Systemic Lupus Erythematosus (SLE), 10 Sjogren Syndrome (SS), and 14 SSc. Salient demographic and clinical characteristics of the study population are reported in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…It is common to associate CP with several autoimmune diseases, such as primary biliary cirrhosis (PBC) or Sjögren syndrome (SS) [6]. Furthermore, one theory contends that those diseases might be manifestations in different organs of an autoimmune reaction against a common autoantigen.…”
Section: Introductionmentioning
confidence: 99%